Effects of Late-Summer Prescribed Fire on Botanical Composition, Soil Cover, and Forage Production in Caucasian Bluestem-Infested Rangeland in the Kansas Smoky Hills: Final Report - Helen Patricia Giefer; Keith R. Harmoney; M. P. Ramirez; A. J. Tajchman; Z. M. Duncan; J. Lemmon; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: Our objective was to examine the effects of late-summer prescribed fire on the frequency and basal cover of Caucasian bluestem (Bothriochloa bladhii), soil cover, botanical composition, and forage production in the Kansas Smoky Hills. Study Description: Eighteen one-acre plots located in a Caucasian bluestem-infested pasture in Ellsworth County, Kansas, were randomly assigned to one of three treatments: no burn (control), one burn (August 14, 2019), and two burns (August 14, 2019, and August 11, 2021). Pre-treatment data were collected in 2019 (year one); measurements of soil cover, botanical composition, forage production, and Caucasian bluestem frequency and basal cover were taken each year thereafter. The Bottom Line: These data suggest that regular application of late-summer prescribed fire may reduce Caucasian bluestem basal cover while having no negative consequences on native species and improving overall grass-species richness.
Keywords: basal cover; late-summer prescribed fire; old-world bluestem